Real‐World Impact of Olaparib Exposure in Advanced Pancreatic Cancer Patients Harboring Germline BRCA1‐2 Pathogenic Variants - Michele Milella; Giulia Orsi; Mariacristina diMarco; Lisa Salvatore; Letizia Procaccio; Silvia Noventa; Silvia Bozzarelli; Ingrid Garajova; Enrico Vasile; Guido Giordano; Marina Macchini; Alessandro Cavaliere; et al. (Cancer Medicine, 2025)
ABSTRACT Introduction Pancreatic cancer arising in the context of BRCA predisposition may benefit from poly(ADP‐ribose) polymerase inhibitors. We analyzed real‐world data on the impact of olaparib on survival in metastatic pancreatic cancer patients harboring germline BRCA mutations in Italy, where olaparib is not reimbursed for this indication. Methods Clinico/pathological data of pancreatic cancer patients with documented BRCA1‐2 germline pathogenic variants who had received first‐line chemotherapy for metastatic disease were collected from 23 Italian oncology departments and the impact of olaparib exposure on overall survival (OS) was analyzed. Results Of 114, 53 BRCA‐mutant pancreatic cancer patients had received olaparib for metastatic disease. OS was significantly longer in patients who were exposed to olaparib (hazard ratio [HR] 0.568, 95% confidence interval [CI] 0.351–0.918, log‐rank p = 0.02) in any setting/line of treatment; similar results were obtained for patients who received olaparib as maintenance treatment (in any line of treatment), patients who had stage IV disease at diagnosis, and patients who did not experience progressive disease as their best response to first‐line chemotherapy. Exposure to olaparib in the first‐line maintenance setting after platinum‐based chemotherapy, however, did not significantly impact survival. At multivariate analysis, CA19.9 levels at diagnosis and response to first‐line chemotherapy were independently prognostic; however, when response to chemotherapy was excluded, any exposure to olaparib was a significant independent predictor of longer OS, together with CA19.9 levels. Conclusion The real‐world data presented here support the use of olaparib for metastatic disease in germline BRCA‐mutant pancreatic cancer patients, as it may significantly prolong survival.